Action in school networks to combat violence: an experience report - Brito Soares, Naiane; Nunes Moraes-Partelli, Adriana; Gasparini Santos, Séfora; Aparecida Ataide, Cintia (Guará Journal, 2025)
Based on formative health education strategies developed through an extension activity, it was found that a significant proportion of teachers in the state public education system were familiar with the definition and types of violence, yet experienced difficulties in identifying and referring children and adolescents who were victims of violence. The objective is to report the experience of an extension action planned by undergraduate Nursing students and implemented for elementary school teachers addressing the theme of violence, with a focus on children and adolescents. This is an experience report related to a health education project carried out in response to a local demand from the school community. The action, organized in the format of a course, comprised six modules, five theoretical and one practical, aimed at the production of educational materials. The course included the participation of lower secondary education teachers from a state school in northern Espírito Santo, Brazil. The students planned, took part in the development, and evaluated the course, which was delivered in 2022. The course entitled “Networking within the school system to address violence” was conducted with the participation of 15 teachers and had a total workload of 20 hours. Finally, training actions grounded in methodologies inspired by Paulo Freire’s pedagogy made it possible, based on the social reality of the target audience, to create a space for discussion and reflection on the theme of violence in a participatory and creative manner, culminating in the development of educational materials on violence.